2020
DOI: 10.1101/2020.06.07.139048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Boundary sequences flanking the mouse tyrosinase locus ensure faithful pattern of gene expression

Abstract: Control of gene expression is dictated by cell-type specific regulatory sequences that physically organize the structure of chromatin, including promoters, enhancers and insulators. While promoters and enhancers convey cell-type specific activating signals, insulators prevent the cross-talk of regulatory elements within adjacent loci and safeguard the specificity of action of promoters and enhancers towards their targets in a tissue specific manner. Using the mouse tyrosinase (Tyr) locus as an experimental mod… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…This observation suggested that the variegated phenotype previously reported in the YAC YRT4, YRT5, and YRT2ΔLCR transgenic mice could be explained by the randomly integrated transgenes, and consequent chromosomal position effects. This experiment also highlighted the relevance of assessing the role of non‐coding DNA regulatory elements in their natural context, an approach that became possible with the arrival of CRISPR‐Cas9 genome‐editing methods (Seruggia et al., 2020; Seruggia et al., 2015; Seruggia & Montoliu, 2016).…”
Section: Third Generation Of Tyr Mouse Models: Crispr‐cas9 Genome‐edimentioning
confidence: 98%
See 3 more Smart Citations
“…This observation suggested that the variegated phenotype previously reported in the YAC YRT4, YRT5, and YRT2ΔLCR transgenic mice could be explained by the randomly integrated transgenes, and consequent chromosomal position effects. This experiment also highlighted the relevance of assessing the role of non‐coding DNA regulatory elements in their natural context, an approach that became possible with the arrival of CRISPR‐Cas9 genome‐editing methods (Seruggia et al., 2020; Seruggia et al., 2015; Seruggia & Montoliu, 2016).…”
Section: Third Generation Of Tyr Mouse Models: Crispr‐cas9 Genome‐edimentioning
confidence: 98%
“…The alignment of the deleted DNA fragments in several independent lines with the same hypopigmented phenotype pointed again to the core element of this 5’ region, including the previously identified hs1/hs2 (box A and B) binding sites for nuclear factors. A detailed histological analysis of the retina from the genome‐edited mice indicated that only the neural crest‐derived melanocytes in the choroid lost Tyr expression and hence showed no pigmentation (Seruggia et al., 2020). By contrast, the RPE layer of cells was normally and uniformly pigmented, thus confirming the notion that the 5’ regulatory element mainly controls Tyr expression in the melanocyte lineage, not in the optic cup‐derived RPE cells.…”
Section: Third Generation Of Tyr Mouse Models: Crispr‐cas9 Genome‐edimentioning
confidence: 99%
See 2 more Smart Citations
“…Describing new genes associated with albinism will also help to reduce the significant number (~30%) of clinically diagnosed people with albinism, where we fail to detect the responsible molecular lesion (Lasseaux et al., 2018; Montoliu et al., 2014). An additional source for detecting new mutations is the non‐coding DNA regulatory elements, which might also contribute to the missing mutations in these undiagnosed patients (Seruggia et al., 2020).…”
Section: Albinism Type Human Gene Human Chromosome Mouse Gene Mouse Cmentioning
confidence: 99%